The Augmented Reality-Based Company Profile Application: A Case Study on the Faculty of Engineering at Universitas Halu Oleo - Rahman, Faizal Jumain; Purnama, Ika Purwanti Ningrum; Sari, Jayanti Yusmah (Digital Innovation, 2025)
This research focuses on the development of an Augmented Reality (AR) based company profile application specifically designed for the Faculty of Engineering at Universitas Halu Oleo. The aim is to create a promotional media that is not only informative but also engaging and interactive, enhancing the faculty's marketing efforts. The application was developed to allow users to access detailed information about the faculty through 3D virtual representations and interactive features that leverage AR technology.The functionality of the application was rigorously tested using black box testing methods to ensure it operates effectively across different devices and under various user interactions. The tests included installation, operation, user interface interactions such as tapping, swiping, and scrolling, and the integration with camera functions for AR features. The results confirmed that the application is fully functional, with all features performing as expected. The AR application supports multiple device resolutions and performs optimally in diverse lighting conditions, proving its robustness and adaptability.This study demonstrates the potential of AR technology as a transformative tool for educational promotion, providing an immersive and interactive experience that can significantly enhance user engagement. The application successfully integrates practical functionality with advanced AR features, making it a valuable asset for the Faculty of Engineering at Universitas Halu Oleo in their ongoing efforts to attract new students and partners.